2020
DOI: 10.1039/c9nr09889e
|View full text |Cite
|
Sign up to set email alerts
|

Realization of a near-infrared active Fano-resonant asymmetric metasurface by precisely controlling the phase transition of Ge2Sb2Te5

Abstract: A metasurface is one of the most effectual platforms for the manipulation of complex optical fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 76 publications
0
37
0
Order By: Relevance
“…Metamaterials 24‐43 and its two‐dimensional (2D) counterpart metasurfaces 44‐68 made from plasmonic resonant 69‐73 or Mie resonant building blocks 74‐84 are especially promising for the enhancement of light–matter interactions 19,85,86 at a subwavelength scale. Various plasmonic and Mie metamaterials have been proposed for achieving high Q factor response, 87‐96 for example, the trapped mode, which is kind of magnetic mode weakly coupled to free space, was suggested to be excited by introducing symmetry breaking in the shape of structural elements for realizing sharp spectral response 87 .…”
Section: Introductionmentioning
confidence: 99%
“…Metamaterials 24‐43 and its two‐dimensional (2D) counterpart metasurfaces 44‐68 made from plasmonic resonant 69‐73 or Mie resonant building blocks 74‐84 are especially promising for the enhancement of light–matter interactions 19,85,86 at a subwavelength scale. Various plasmonic and Mie metamaterials have been proposed for achieving high Q factor response, 87‐96 for example, the trapped mode, which is kind of magnetic mode weakly coupled to free space, was suggested to be excited by introducing symmetry breaking in the shape of structural elements for realizing sharp spectral response 87 .…”
Section: Introductionmentioning
confidence: 99%
“…Metamaterials consist of arrays of resonant elements designed to resonate with incident electromagnetic waves at specific frequencies [ 10 , 11 , 12 ]. Terahertz metamaterials have received significant attention in the field of biosensors, where they can overcome problems of low-scattering cross section by their highly confined electric fields when on-resonance [ 13 , 14 , 15 , 16 , 17 ], while also affording a degree of tunability [ 18 , 19 , 20 , 21 , 22 , 23 ]. We recently demonstrated that THz metamaterials can be used to measure the permittivity of thin films and liquids at the resonant frequency of metamaterials using free-space THz-TDS measurements [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, there have been papers claiming multilevel switching of GST metasurface, but they relied on the partial crystallization of thick GST that cannot be quantitatively controlled owing to the nonprecise molecular dynamics of GST. [ 41–44 ] Hence, their multilevel switchable functionality is limited to only spectrum modulation of input light that cannot be precisely predictable. On the other hand, our proposed GST metasurface can switch its state at will through applying specified conditions of control light as proven in Section 2.1.…”
Section: Resultsmentioning
confidence: 99%